Archaeologists, tourists, interpreters : exploring Egypt and the Near East in the late 19th-early 20th centuries /: exploring Egypt and the Near East in the late 19th-early 20th centuries. (2015 copyright 2015) - Mairs, Rachel; Muratov, Maya
No abstract available